KONVERSI HUKUM ADAT DALAM SISTIM HUKUM SUMBERDAYA LAUT DI INDONESIA - M Ridwan (IAIN Ambon, 2021)
Abstract: The Unitary State of the Republic of Indonesia is an archipelagic country, has marine resources, developed to help the region achieve economic, social and political goals. This study focuses on phenomena arising from the management of Indonesia's marine fisheries resources. The implementation of the law creates conflicts of interest between the regions and the central government. This study uses a juridical approach based on a statutory approach and a conceptual approach based on constructiveness principles with data collection techniques for legal materials taken from various literatures in the form of statutory regulations, principles, theories, concepts. ¬ concepts and / or opinions of legal and social experts. The results of the research show that the material contained in the laws and regulations related to the management of marine fisheries resources has not provided the greatest benefit for the prosperity of the people so that the conversion of sasi customary law is needed to find laws that are in accordance with the characteristics of Indonesia as an archipelagic country.